Changes in taste and odor sensitivities during repeated bicycle ergometer exercises - Masataka Narukawa; Kensuke Nojiri; Rina Matsuda; Momo Murata; Seiji Sakate; Sachiko Kuga; Hidetoshi Ue (Journal of the International Society of Sports Nutrition)
Background Effective nutritional support is essential for maintaining good performance during exercise. Taste and olfaction are key senses for food intake, and understanding how their sensitivities change during exercise is important for effective nutritional support. However, the effects of exercise on taste and odor sensitivities remain unclear. This study aimed to investigate changes in taste and odor sensitivities during repeated endurance exercise using a bicycle ergometer.Methods A total of 20 women (mean age; 21.6 ± 0.2 years) participated in the study, completing four 60-minute segments, each comprising 50 minutes of bicycle ergometer exercise at an exercise intensity of 60% heart rate reserve and a 10-minute sensory test. The sensory tests were conducted five times in total: after each exercise segment and once before exercise as a control. Four concentrations (×0.5, ×0.75, ×1, and × 1.25) of a commercially available isotonic beverage were used as taste samples, and the subjects evaluated the taste intensity, preference, and odor intensity. Four types of food odorants were used as odor samples, and the subjects rated their preference. The subjects also reported their perceived fatigue levels during the taste and odor tests. Fatigue levels and taste intensity were rated using a 100-mm visual analogue scale, and taste and odor preferences and odor intensity were evaluated using a scoring method.Results The degree of physical fatigue significantly increased with each successive bicycle exercise segment. The taste intensity and preference for beverages with higher concentrations increased as the number of exercise segments increased, showing a significant increase in taste intensity for the × 1.25 solution in the final segment compared with before the tests. On the other hand, no significant effect was observed on the perceived odor intensity of the isotonic beverages. Similarly, there was no significant effect on the preference for odor samples due to repeated exercise.Conclusions These results suggest that taste sensitivity may change with prolonged exercise. Additionally, since odor intensity and preference were not significantly affected by repeated exercise, odor sensitivity may be less impacted by exercise than taste sensitivity.